Ascitic calprotectin as a diagnostic marker for spontaneous bacterial peritonitis in hepatitis C virus cirrhotic Egyptian patients - Ahmed A Heikl; Mahmoud M El-Nokeety; Eman Roshdy; Abeer Mohey (The Egyptian Journal of Internal Medicine, 2018)
Background The gold standard for the diagnosis of spontaneous bacterial peritonitis (SBP) is a polymorphonuclear leukocyte (PMNL) count of 250/mm3or more. Accurate and early diagnosis of SBP is important to decrease the mortality and complications in patients with cirrhosis. Aims The aim of this study was to evaluate the accuracy of ascitic fluid calprotectin as a diagnostic marker for the detection of SBP. Patients and methods Seventy Egyptian patients with liver cirrhosis and ascites were enrolled; these patients were divided into two groups: 50 patients with SBP and 20 patients with no SBP on the basis of an elevated ascitic PMNL count of 250 cells/mm3 or more. Ascitic samples were examined for PMNL count, culture, chemistry, and calprotectin concentrations in all patients. Results Calprotectin levels in ascitic fluid were correlated significantly with PMNLs and significantly higher in patients with SBP than non-SBP (P<0.001), with the best cutoff value for the detection of SBP of 783 ng/ml with a sensitivity, a specificity, a positive predictive value and negative predictive value, and an accuracy of 90, 100, 100, 80, and 92.9%, respectively. Conclusion Elevated ascitic calprotectin levels in cirrhotic patients are a diagnostic and reliable marker for the detection of SBP and considered a surrogate marker for PMNL.